Plastic surgery in a medium complexity hospital: prospective cohort with cost and results analysis of the treatment of skin tumors within the scope of the Unified Health System (SUS) - Daniele Walter Duarte (Revista Brasileira de Cirurgia Plástica)
Introduction: The Brazilian health system is organized into basic health units, medium complexity hospitals, and high complexity hospitals. The composition of medium complexity services is variable, with or without specialists such as the plastic surgeon. The objective of the present study is to analyze data on the treatment of patients with skin tumors by a plastic surgeon in a medium complexity hospital. Methods: prospective cohort with analysis of epidemiological, demographic data, costs, results, complications, and degree of satisfaction. Results: In nine months, 166 patients were treated, of whom 103 underwent surgery. The most common pathologies were: basal cell carcinomas, benign subcutaneous and cutaneous tumors, squamous cell carcinoma and melanoma, in decreasing order of appearance. Most of the injuries were treated with exeresis and suture surgery and in 29 patients, more complex reconstructions were required. The degree of resolution of cases was high, and only a patient was derived to a high complexity hospital. The degree of satisfaction with the treatment was also high. However, the estimated financial transfer of SUS, in the case of malignant tumors treatment, was approximately 25% less than it is in a high complexity hospital. Conclusion: The role of the plastic surgeon in medium complexity hospitals can prevent diseases such as skin cancer from reaching high complexity hospitals in advanced stages. However, there would have to be adaptations in the government transfer to enable the routine performance of this professional in these institutions.